(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Strategy formulation has increasingly gained recognition and traction among top and medium-level organizations because of its ability to improve organizational performance. In the current globalization era, strategic management practices have been considered among the most significant practices that distinguish organizations from others. As a key sector, healthcare continues to attract private investors who want to provide medical services and make profits just like other entrepreneurs. This study established the effect of strategy formulation on the organizational performance of selected private hospitals in Bungoma County, Kenya. The study was anchored on two theories, including management by objectives theory as the main theory, supported by Resource-based theory. The explanatory research design was used for this study. The study targeted a population of 149 respondents that includes; managers, directors, marketing officers, and board of management representatives. The sample size involved participants distributed across the thirty-eight selected private hospitals in the county. A five-point Likert scale on the data was used on the data collection instruments. Pilot study was carried out in three private hospitals in Kakamega County for validity of the research instrument. For reliability analysis, Cronbach’s alpha was used which recommends a minimum threshold of 0.7. Descriptive statistics was used to analyze data involving means, percentages and frequencies. Findings indicated that Strategy formulation (r=0.891, p=000) has a statistically significant effect on organizational performance. The study recommended that private hospitals in Bungoma should embrace strategy formulation to enhance their organizational performance.